2013
DOI: 10.1371/journal.pgen.1003186
|View full text |Cite
|
Sign up to set email alerts
|

Rbfox1 Downregulation and Altered Calpain 3 Splicing by FRG1 in a Mouse Model of Facioscapulohumeral Muscular Dystrophy (FSHD)

Abstract: Facioscapulohumeral muscular dystrophy (FSHD) is a common muscle disease whose molecular pathogenesis remains largely unknown. Over-expression of FSHD region gene 1 (FRG1) in mice, frogs, and worms perturbs muscle development and causes FSHD–like phenotypes. FRG1 has been implicated in splicing, and we asked how splicing might be involved in FSHD by conducting a genome-wide analysis in FRG1 mice. We find that splicing perturbations parallel the responses of different muscles to FRG1 over-expression and disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 85 publications
1
36
0
Order By: Relevance
“…A recent study indicated that the knockdown of Rbfox1 inhibits muscle differentiation, and that RBFOX1 expression was altered in a mouse model of facioscapulohumeral muscular dystrophy [64]. We identified 34 RBFOX1 targets in muscle-relevant genes ( Fig.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study indicated that the knockdown of Rbfox1 inhibits muscle differentiation, and that RBFOX1 expression was altered in a mouse model of facioscapulohumeral muscular dystrophy [64]. We identified 34 RBFOX1 targets in muscle-relevant genes ( Fig.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, we have previously shown collective alternative splicing of several transcripts in distinct temporal clusters during myoblast differentiation however it is not well understood if these muscle-specific protein isoforms cooperate to control specific aspects of the myogenic program (Bland et al, 2010). Misregulated splicing contributes to disease phenotypes in skeletal muscle in diseases such as myotonic dystrophy (DM) and facioscapulohumeral muscular dystrophy (FSHD) demonstrating an essential role of regulated splicing for proper skeletal muscle function (Gabellini et al, 2006; Pistoni et al, 2013; Singh and Cooper, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Third, only selective muscles in FRG1-overexpressing mice are dystrophic and display altered accumulation of myosin heavy chain (MyHC) (8). Finally, it has been shown that in muscles of both FSHD patients and FRG1 transgenic mice, specific pre-mRNAs undergo aberrant alternative splicing (13,34). In particular, our previous studies revealed the aberrant splicing of the fast skeletal troponin T (TNNT3) mRNA in muscles from FRG1 transgenics, as well as in myoblasts of FSHD patients (13).…”
mentioning
confidence: 99%